Marketing i muzejsko izdavaštvo - Šola, Tomislav (2002)
Both major categories of museum publishing (1-museum publishing as a part of a complex museum product ; 2-publishing whose aim is to announce and popularise the museum product and make it attractive or use ot to accompany some event in order to clarify or to earn an income) are relevant themes for marketing. Marketing is the motive, the will and ability to create a quality product, and it is also at the same time a systematic attempt to publicise the product. Therefore, everything that is linked with the museum is the subject of a marketing theme, so that this all-embacing aspect also refers to publishing.
Projekt MZOS
HRV